Enhancing the processibility of high temperature polymerizing cardanol derived benzoxazines using eco-friendly curing accelerators. (28th February 2018) - Sharma, Pratibha; Kumar, Devendra; Roy, Prasun Kumar
Abstract: The advent of bio-based benzoxazine in the field of polybenzoxazines is a major breakthrough towards their sustainable development. Cardanol derived benzoxazine offers solvent less synthesis and processing benefits over the petro based resin, however these mandate high curing temperatures. The polymerization temperature can be alleviated through structural modifications or physical blending with curing accelerators; the latter approach being preferred in view of its economic viability. Most of the curing accelerators are moisture sensitive, which adversely affect the end performance of the polymer. In this paper, the potential of eco-friendly stearates based on transition metals as curing accelerators for the polymerization of cardanol based benzoxazine resin has been demonstrated. Metal stearates were formulated with bio-based monomer which leads to significant lowering of the curing profiles, the extent of which was proportional to the amount of accelerator. The hydrophobicity associated with the long alkyl chain in stearate bestows it hydrolytic stability, which allows its use under ambient conditions without special caution. Zinc(II) stearate exhibit highest activity towards acceleration and its inclusion does not alter the viscosity of the formulation offering a processing advantage. Kinetic parameters associated with polymerization of the resin were established using Kissinger Akahira Sunose method. Graphical abstract: Highlights: Transition metal stearates were explored as curing accelerators. Inclusion of zinc stearate led to a remarkable reduction in the polymerization temperature of the bio-based resin. Rheological behavior of the resin was not adversely affected due to the inclusion of zinc stearate. Activation energy of the polymerization of benzoxazine resin was calculated using KAS method. Polymer with improved thermal stability was obtained using zinc stearate as curing accelerator.